Slovak geomagnetic repeat stations – the 2006.5 epoch - VALACH, Fridrich; VÁCZYOVÁ, Magdaléna; DOLINSKÝ, Peter (Contributions to Geophysics and Geodesy, 2021)
The Slovak repeat station network consists of six stations. It was established in 2004 in a way to provide long time series of geomagnetic measurements at the same, or nearly the same, places, with the beginning in the middle of the 19th century. The new geomagnetic network was measured first time in 2004. It was reoccupied in the middle of 2006. In this paper, long time series of three geomagnetic elements D, I and F at the repeat stations are completed, the results of the last geomagnetic measurements, reduced to the 2006.5 epoch, are presented, and a comparison with those from the 2004.5 epoch is performed.